A short review on nano-additives to enhance biodiesel performance in diesel engines - Jathar, Laxmikant D.; Meherunnesa; Shelare, Sagar; Shahapurkar, Kiran; Abedin, Tarek; Farade, Rizwan A.; Rajabi, Armin; Khan, T. M. Yunus; Singh, Ramesh; Cuce, Erdem; Nur-E-Alam, Mohammad (Science Press, 2025)
Vegetable oils and animal fats-sourced biodiesel are considered a promising alternative to conventional diesel fuel. However, they possess convinced restrictions like inadequate cold flow properties, poor lubricity, and complex emissions of nitrogen oxides (NOx). However, various nano-additives have emerged to overcome those limitations and enhance the performance of biodiesel in diesel engines. The impact of different additives on diesel engine characteristics that have been conducted recently with the combination of biodiesel is thoroughly analyzed in this review paper. Additionally, to provide a thorough summary of experimental research done in this area, the article addresses the several kinds of additives that are frequently employed and their effects on engine performance, combustion, emissions, wear, and durability. The evaluation of nano-additives’ impacts in diesel-biodiesel engines highlights significant improvements in emissions, combustion efficiency, and engine durability. For example, the multi-walled carbon nanotubes (MWCNT) are found to increase Brake Thermal Efficiency (BTE) by up to 36.81%, while cerium oxide (CeO2) can reduce Brake Specific Fuel Consumption (BSFC) by as much as 30%. Additionally, titanium dioxide (TiO2) achieves a minimum NOx reduction of 22.57%, and graphene nanoplatelets (GNPs) have produced a minimum 65% reduction in carbon monoxide (CO) emissions, albeit with higher hydrocarbons (HC) emissions. However, long-term engine durability studies are needed to assess the compatibility of nano-additives with engine components and their impact on engine longevity which could be the future research direction aiming to investigate new nanoparticle possibilities and reduce pollutants to maximize biodiesel performance.